Antioxidative Coumarins from the Roots of Ferulago subvelutina - Naseri, M.; Monsef-Esfehani, H.R.; Saeidnia, S.; Dastan, D.; Gohari, A.R. (Asian Journal of Chemistry, 2012)
From the ethyl acetate extract of the roots of Ferulago subvelutina (Apiaceae) six coumarins, osthol (1), oxypeucedanin (2), xanthotoxin (3), isoimperatorin (4), oxypeucedanin hydrate (5), meranzine hydrate (6) and one sterol, b-sitosteryl linoleate (7), were isolated by silica gel column chromatography and identified by spectroscopic methods. Antioxidant activities of the isolated compounds were tested by the DPPH radical scavenging assay. Compounds exhibited moderate antioxidant activities. DPPH scavenging abilities of compounds were lower than that of synthetic antioxidant tert-butyl hydroxytoluene (BHT) (IC50 = 27 μg/mL) in the order BHT > oxypeucedanin hydrate > meranzin hydrate > oxypeucedanin > isoimperaturin > xanthotoxin > osthole.